Sphingosine 1-phosphate (S1P) signalling: Role in bone biology and potential therapeutic target for bone repair. (November 2017) - Sartawi, Ziad; Schipani, Ernestina; Ryan, Katie B.; Waeber, Christian
Graphical abstract: Abstract: The lipid mediator sphingosine 1-phosphate (S1P) affects cellular functions in most systems. Interest in its therapeutic potential has increased following the discovery of its G protein-coupled receptors and the recent availability of agents that can be safely administered in humans. Although the role of S1P in bone biology has been the focus of much less research than its role in the nervous, cardiovascular and immune systems, it is becoming clear that this lipid influences many of the functions, pathways and cell types that play a key role in bone maintenance and repair. Indeed, S1P is implicated in many osteogenesis-related processes including stem cell recruitment and subsequent differentiation, differentiation and survival of osteoblasts, and coupling of the latter cell type with osteoclasts. In addition, S1P's role in promoting angiogenesis is well-established. The pleiotropic effects of S1P on bone and blood vessels have significant potential therapeutic implications, as current therapeutic approaches for critical bone defects show significant limitations. Because of the complex effects of S1P on bone, the pharmacology of S1P-like agents and their physico-chemical properties, it is likely that therapeutic delivery of S1P agents will offer significant advantages compared to larger molecular weight factors. Hence, it is important to explore novel methods of utilizing S1P agents therapeutically, and improve our understanding of how S1P and its receptors modulate bone physiology and repair.